HETEROPLASMY IN HUMAN MITOCHONDRIAL DNA - Dwiyanti (NIm 20504008), Faika
ABSTRACT: Identification process through sequence determination of hypervariable segment I (HVSI) of mitochondrial DNA (mtDNA) could be done due to its high mutation rate. However, T16189C mutation, which leads to poli-cytosin stretch (poli-C), gives rise to the incompletion of sequence determination through direct sequencing shown by the unread sequences after the stretch. This problem has been solved using cloning method. Hypothetically, the failure of direct sequencing and the success of sequencing after cloning happened due to heteroplasmy phenomena. Several recombinant DNA clones of samples that have poli-C stretch are sequenced using Dideoxy Sanger method to test this hypothesis. Three out of four clones of GMR samples have 11C-long and the other has 12C-long poli-C stretch. Whereas for XXAM sample, two clones showed different length of poli-C stretch, i.e. 12C and 15C. This work has successfully shown the existence of heteroplasmy that can be proposed as the cause of incompletion in mtDNA HVSI sequence determination of sample containing poli-C stretch through direct sequencing.